The Future of AI in Public Policy, Healthcare, and Finance: Opportunities and Challenges - Nawaz, Ali; Yaseen, Abid; Abid, Touseef; Butt, Rabia; Ashraf, Shafaq (Journal of Neonatal Surgery, 2025)
Artificial intelligence (AI) is increasingly reshaping public policy, healthcare, and finance, offering transformative opportunities for decision-making, service delivery, and risk management. This study employed a mixed-methods design to examine sector-specific AI adoption, perceived benefits, and challenges across North America, Europe, and Asia. Quantitative data were collected via a survey of 300 professionals, while qualitative insights were obtained from 15 semi-structured expert interviews. Findings revealed that healthcare professionals prioritized early diagnostics and personalized treatment, finance professionals emphasized fraud detection and risk assessment, and public policy stakeholders highlighted improved decision-making and citizen engagement. Key challenges included high implementation costs, data privacy concerns, algorithmic bias, and lack of transparency. Thematic analysis of interviews underscored the importance of ethical governance, workforce readiness, global equity, and trust in AI systems. Overall, the study highlights the need for responsible, transparent, and inclusive AI strategies to maximize benefits while mitigating risks, providing actionable insights for policymakers, practitioners, and researchers.